Strengthening Carving Business Management in Siangan Village, Gianyar, Bali - Partiwi Dwi Astuti; Ni Putu Riasning (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Strengthening the management of the carving business is necessary because the existence of this business provides high economic value and has the potential to go global, so that the business is required to be able to face competition, generate product growth with new innovations, technological renewal, create jobs and improve the welfare of the local community. This community service was carried out in Siangan Village, Gianyar, Bali. The purpose of this community service activity is to increase knowledge of the role of the marketing mix, understanding of financial management and entrepreneurial knowledge of carving businesses. The method used to strengthen the management of the carving business is community education through counseling. The results of this community service show that there is an increase of 20% related to knowledge about the role of marketing mix, understanding of financial management and entrepreneurial knowledge of carving business actors.